Optimisation of a novel series of potent and orally bioavailable azanaphthyridine SYK inhibitors. Issue 19 (1st October 2016) - Garton, Neil S.; Barker, Michael D.; Davis, Rob P.; Douault, Clement; Hooper-Greenhill, Edward; Jones, Emma; Lewis, Huw D.; Liddle, John; Lugo, Dave; McCleary, Scott; Preston, Alex G.S.; Ramirez-Molina, Cesar; et al.
Graphical abstract: Abstract: The optimisation of the azanaphthyridine series of Spleen Tyrosine Kinase inhibitors is described. The medicinal chemistry strategy was focused on optimising the human whole blood activity whilst achieving a sufficient margin over hERG activity. A good pharmacokinetic profile was achieved by modification of the p K a . Morpholine compound32 is a potent SYK inhibitor showing moderate selectivity, good oral bioavailability and good efficacy in the rat Arthus model but demonstrated a genotoxic potential in the Ames assay.